2015
DOI: 10.1038/am.2015.36
|View full text |Cite
|
Sign up to set email alerts
|

High thermoelectric performance of all-oxide heterostructures with carrier double-barrier filtering effect

Abstract: Thermoelectric materials can realize significant energy savings by generating electricity from untapped waste heat; however, the coupling of the thermoelectric parameters unfortunately limits their efficiency and practical applications. Herein, rational all-oxide TiC 1-x O x @TiO y -TiO 2 (xo1, 1oyo2) heterostructures with significantly enhanced thermoelectric properties have been designed, and a high dimensionless figure of merit (ZT) value of up to 0.84 at 973 K was achieved in the all-oxide TiC 0.1 O 0.9 @T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 69 publications
1
37
1
Order By: Relevance
“…However, PbTe and Bi 2 Te 3 are not suitable for widespread adoption due to the low abundance of Te, and there are also concerns with SnSe due to the environmental toxicity of Se. There has therefore been significant effort devoted to alternative systems including the more earth-abundant SnS [2] and metal oxides [7][8][9][10].Alloying is commonly used as a means to enhance thermoelectric performance, as a suitable choice of components can maintain or improve a favourable electronic structure while reducing k latt by introducing variation in atomic masses and chemical bond strength to promote stronger phonon scattering [11]. Pb(S, Se, Te), Sn(S, Se) and (Bi, Sb) 2 (Se, Te) 3 alloys have all been studied as thermoelectrics and the alloying shown to improve ZT [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…However, PbTe and Bi 2 Te 3 are not suitable for widespread adoption due to the low abundance of Te, and there are also concerns with SnSe due to the environmental toxicity of Se. There has therefore been significant effort devoted to alternative systems including the more earth-abundant SnS [2] and metal oxides [7][8][9][10].Alloying is commonly used as a means to enhance thermoelectric performance, as a suitable choice of components can maintain or improve a favourable electronic structure while reducing k latt by introducing variation in atomic masses and chemical bond strength to promote stronger phonon scattering [11]. Pb(S, Se, Te), Sn(S, Se) and (Bi, Sb) 2 (Se, Te) 3 alloys have all been studied as thermoelectrics and the alloying shown to improve ZT [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Many approaches have been developed in the recent years to enhance the thermoelectric power factor ( S 2 / ρ ) including modifying the band structure by electronic resonant states, [ 4 ] quantum confi nement effects, [ 5 ] band convergence, [ 6 ] energy barrier fi ltering, [ 7,8 ] and intensifying impurity scattering of the carriers [ 9 ] to enhance the Seebeck coefficient. Many approaches have been developed in the recent years to enhance the thermoelectric power factor ( S 2 / ρ ) including modifying the band structure by electronic resonant states, [ 4 ] quantum confi nement effects, [ 5 ] band convergence, [ 6 ] energy barrier fi ltering, [ 7,8 ] and intensifying impurity scattering of the carriers [ 9 ] to enhance the Seebeck coefficient.…”
mentioning
confidence: 99%
“…
wileyonlinelibrary.comthe Seebeck coeffi cient is related to the electrical conductivity according to the Boltzmann transport equations, [ 3 ] hence, it will be hard to optimize one without degrading the other. Many approaches have been developed in the recent years to enhance the thermoelectric power factor ( S 2 / ρ ) including modifying the band structure by electronic resonant states, [ 4 ] quantum confi nement effects, [ 5 ] band convergence, [ 6 ] energy barrier fi ltering, [ 7,8 ] and intensifying impurity scattering of the carriers [ 9 ] to enhance the Seebeck coefficient. Among these, the carrier impurity scattering effect on the Seebeck coeffi cient has been recently investigated in Skutterudite [ 9 ] after it had nearly been ignored during the past half century.
…”
mentioning
confidence: 99%
“…Furthermore, the large operating temperature difference has its own contribution, but ultimately it is all about the material's ability to convert heat and generate usefule lectric power. Recently, many new classes of materials,s uch as metal sulfides, [10] selenides, [11] half-Heusler compounds, [12] filled skutterudites, [13] clathrates, [14] oxides, [15] organic or polymer materials, [16] Zintl compounds, [17] and carbon-based compounds, [18] have been introduced with promising properties that give new hopes for the future of thermoelectric technology.F urthermore, strategies such as doping, [19] nanostructuring, [20] alloying, [21] resonant level filling, [22] and band engineering [23] have also been successful in improving the ZT value of the materials. [9] They were preferred for such applications even thought he conversion efficiency was very low because of to their ability to reliably generate poweri nr emote areas without any need for complex technology.D uring 21st century,b etter thermoelectric materials have been developed that are able to expand application of such devices.…”
Section: Thermoelectric Generatorsmentioning
confidence: 99%
“…[9] Earlier,o nly af ew wellknown thermoelectric materials were being used for making thermoelectric generators, which limited their use. Recently, many new classes of materials,s uch as metal sulfides, [10] selenides, [11] half-Heusler compounds, [12] filled skutterudites, [13] clathrates, [14] oxides, [15] organic or polymer materials, [16] Zintl compounds, [17] and carbon-based compounds, [18] have been introduced with promising properties that give new hopes for the future of thermoelectric technology.F urthermore, strategies such as doping, [19] nanostructuring, [20] alloying, [21] resonant level filling, [22] and band engineering [23] have also been successful in improving the ZT value of the materials. For example,m any studies have shown clear improvements in the ZT values of bulk materials by just bringing them to nanostructured dimensions.…”
Section: Thermoelectric Generatorsmentioning
confidence: 99%